Performance Evaluation of Laser Guided Land Leveler in Vertisols of Central India - Chaudhuri, D; Mathankar, S K; Singh, V V; Shirsat, N A; Dubey, U C (Journal of Agricultural Engineering, 2007)
Field experiments were carried out to evaluate the performance of laser guided land leveler for land leveling and grading operations to determine its effect on water requirements and yield of selected crops. Comparison was made with fields in which leveling/grading was done conventionally with drag scraper and also with unleveled fields. The standard deviation of reduced levels and leveling index values ranged from 0.43 to 0.50 cm and 0.29 to 0.34 cm respectively in case of fields leveled/graded by laser guided land leveler. In case of conventional method, the standard deviation of reduced levels and leveling index ranged from 1.39 to 2.81 cm and 0.92 to 2.13 cm respectively. Field capacity of the laser guided land leveler, both in terms of area covered and volume of soil handled per hour was less as compared to conventional leveling grading by drag scraper of same size. The cost of leveling by laser guided land leveler was about 50% higher in case of land leveling operation and nearly double in case of land grading operations as compared to conventional leveling and grading. In the case of paddy crop, land leveling by laser guided land leveler resulted in much lesser variations in height of standing water as a result of which 16.67 % water saving was observed per irrigation. Crop yields were higher in case of fields laser leveled and graded fields. However, differences were significant in the case of paddy and pigeon pea crop only.